2020
DOI: 10.1038/s41598-020-71449-1
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin attenuates isoprenaline-induced cardiac oxidative stress by stimulating multiple antioxidant and anti-inflammatory signaling pathways

Abstract: The antidiabetic drug canagliflozin is reported to possess several cardioprotective effects. However, no studies have investigated protective effects of canagliflozin in isoprenaline (ISO)-induced cardiac oxidative damage-a model mimicking sympathetic nervous system (SNS) overstimulation-evoked cardiac injuries in humans. Therefore, we investigated protective effects of canagliflozin in ISOinduced cardiac oxidative stress, and their underlying molecular mechanisms in Long-Evans rat heart and in HL-1 cardiomyoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 62 publications
6
50
1
1
Order By: Relevance
“…These results indicated that CAN affects glucose and lipid metabolism and then improves heart dysfunctions likely by targeting kidney SGLT2 and promoting urine glucose excretion. However, in another non-diabetic model, CAN did not affect glucose and lipid metabolism but still improved heart functions (Hasan et al, 2020). Our present result in vitro also indicated that CAN exerts a direct protective effect in cardiomyocytes independently of glucose and lipid metabolism.…”
Section: Discussionsupporting
confidence: 61%
“…These results indicated that CAN affects glucose and lipid metabolism and then improves heart dysfunctions likely by targeting kidney SGLT2 and promoting urine glucose excretion. However, in another non-diabetic model, CAN did not affect glucose and lipid metabolism but still improved heart functions (Hasan et al, 2020). Our present result in vitro also indicated that CAN exerts a direct protective effect in cardiomyocytes independently of glucose and lipid metabolism.…”
Section: Discussionsupporting
confidence: 61%
“…SGLT2 inhibitors including empagliflozin have been shown to have a wide range of effects in the cardiovascular system and beyond [ 5 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] Although they are primarily recommended for decreasing renal glucose reabsorption by selectively blocking SGLT2 [ 55 ], this class of drugs appears to have many other molecular targets that result in a range of glucose independent beneficial effects or ‘pleiotropic’ effects. Since SGTL2 has the highest concentration in the renal proximal tubule, the vasodilatory action of empagliflozin in mesenteric artery may be another example of a pleiotropic effect of SGLT2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the interval-ratio data with normal distribution, we performed unpaired Student’s t -tests (two-tailed) to test hypotheses. A p value of <0.05 was considered statistically significant [ 28 , 29 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AMPK improves NO bioavailability by downregulating NOX4 expression, as demonstrated by studies using different drugs able to active AMPK [59]. For instance, Hasan et al have recently demonstrated that canagliflozin, a sodium-glucose cotransporter 2 (SGLT2) inhibitor used in T2DM treatment, ameliorates a cardiac oxidative microenvironment by AMPK/NOX4 signaling [60]. In the same manner, SIRT1 plays a fundamental role in eNO expression.…”
Section: From Caloric Restriction To Caloric Restriction Mimeticsmentioning
confidence: 99%